Pembelajaran berbasis teknologi (blended learning flipped classroom), Integrasi teknologi dalam pembelajaran di MI - Nya Abelia Fitri; Izatum Mufida; Nadia Ayu Wulandari; Dea Intan Nuraini; Suttrisno (Global Action and Education for Society, 2026)
This research was conducted to find out how effective the blended learning learning method is for thematic learning in increasing student learning independence. The results of the observation of learning in pre-cycle students experience difficulties in learning independently due to a lack of motivation from the teacher and confusion in understanding and finding references to subject matter. This research is a classroom action research with blended learning variables to increase learning independence. From the implementation of the actions of cycle II, it is known that there is an increase in learning independence through the Blended Learning approach. It can be seen from (1) the criteria for learning independence, namely the average score of the selfconfidence aspect is 81.43; discipline aspect 81.07 ; initiative aspect 79.64 ; and aspects of responsibility 82.14. The average score for each aspect has reached the minimum completeness criteria, namely 75. (2) where the average student score increases from cycle I (before action) which is 62.14 and in cycle II is 77, 14. (3) Learning completeness also increased from cycle I, namely 42.86% to 85.71% in cycle II. Thus thematic learning with a blended learning approach is said to be successful. As for the advantages and disadvantages of blended learning, the advantages of this approach include that students are more active in learning, learning is more varied and interesting with various learning support platforms, and student learning independence increases. While the weaknesses are such as if the teacher does not master the learning support platform, the learning objectives will not be achieved.